Effect of Aureomycin on the Behaviour of Certain Free Amino Acids in Oil Sardine (Sardinella longiceps) held in Ice Storage - Jacob, Susamma; Karthiayani, T C; Nair, M Rajendranathan (Fishery Technology, 1964)
Effect of Aureomycin on the Behaviour of Certain Free Amino Acids in Oil Sardine (Sardinella longiceps) held in Ice Storage